Evaluation of hormonal changes in obese individuals with constipation problems (Annals of Medical Research, 2024)
Aim: Constipation is frequently seen in obese individuals. It is still not fully known whether the constipation in these individuals is related only to excess weight or due to other reasons. It is limited that the hormones secreted from the gut can play an important role in constipation. In this study, we think that hormones such as intestinal peptide YY, somatostatin, GLP-1, GLP-2 and Oxyntomodulin, which are known to have effects on bowel movements, may have effects on constipation. In this study, it will be tried to determine how the changes in the levels of the mentioned hormones with constipation in individuals who are obese and have constipation problems.Materials and Methods: 22 obese and 22 obese+constipated individuals aged 20-64 years with BMI>30 who would sign the voluntary consent form were included in the study. Individuals with chronic diseases such as diabetes and hypertension in addition to obesity, those who received psychiatric treatment and those who used alcohol were not accepted. The demographic information of the individuals was determined by the face-to-face survey method. GLP-1, GLP-2, somatostatin, peptide YY, serotonin, oxyntomodulin levels were determined with the help of commercial ELISA kit in fasting blood samples taken from obese and obese+constipated individuals in the morning.Results: The levels of oxyntomodulin, PYY, somatostatin did not differ in obese and constipated individuals (p>0.05). GLP-1, GLP-2, serotonin levels were found to be significantly higher in obese individuals than in constipated individuals (p
Keywords: Constipation; Obesity; Peptide YY; Somatostatin; Serotonin; Oxyntomodulin.